Coronavirus Disease-19 associated arthritis – An observational study - Debanjali Sinha; Sumantro Mondal; Alakendu Ghosh (Indian Journal of Rheumatology)
Background: The coronavirus disease or COVID-19 pandemic is the major global health crisis of the present time. Various rheumatological manifestations have been reported during or after COVID-19 infection, but data are scarce. In this observational study, we have tried to analyze the clinical characteristics of COVID-19 associated arthralgia/arthritis. Methods: We have collected the clinical data of 14 patients over the past 6 months who have developed arthralgia or arthritis during or after symptomatic COVID-19 infection, proven by a positive reverse transcription-polymerase chain reaction test from nasopharyngeal swab. Results: The most common symptoms during COVID-19 infection in the 14 patients were fever and myalgia, being present in 92.8% and 64.3% patients, respectively. Arthralgia/arthritis occurred at a mean interval of 20 days (range: 0–60 days). Knee was the most commonly involved joint (78.6%), followed by the wrist and metacarpophalangeal joints (each in 57.1%). Enthesitis was documented in 21.4% patients. The mean duration of COVID-19 associated arthralgia or arthritis was 53.9 days (range: 7–210 days). In 85.7% patients, joint pains improved within 2 months; in only a small proportion of patients (14.3%), joint pains persisted after 6 months. Nonsteroidal anti-inflammatory drugs (NSAIDs) (given in 64.3% patients) and corticosteroids (in 50%) were the most commonly prescribed and effective treatment options. Conclusion: COVID-19 infections mostly caused reactive arthritis, though acute and chronic arthritis is also seen. In the majority of cases, arthritis started about 3 weeks after COVID-19 infection and subsided within 2 months. NSAIDs and corticosteroids are the most effective treatment options.